2012
DOI: 10.1097/pec.0b013e3182442eeb
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients Visiting the Pediatric Emergency Service in an Egyptian University Hospital

Abstract: Appropriate and ongoing data collection and analysis could guide more efficient utilization of pediatric emergency services to achieve better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
3
13
4
Order By: Relevance
“…Poor maternal health and low birth weight are just some of the risk factors for any type of CP. The lower social class was found to be the most common social class for the development of CP, which is in harmony with other studies in Africa; the time of brain insult during prenatal, antenatal, and acquired causes agrees with other studies [26][27][28]. Birth asphyxia was presented as the main etiological cause of CP that occurs prenatally, followed by neonatal jaundice; this is in harmony with a study done in Nigeria [29].…”
Section: Discussionsupporting
confidence: 89%
“…Poor maternal health and low birth weight are just some of the risk factors for any type of CP. The lower social class was found to be the most common social class for the development of CP, which is in harmony with other studies in Africa; the time of brain insult during prenatal, antenatal, and acquired causes agrees with other studies [26][27][28]. Birth asphyxia was presented as the main etiological cause of CP that occurs prenatally, followed by neonatal jaundice; this is in harmony with a study done in Nigeria [29].…”
Section: Discussionsupporting
confidence: 89%
“…A global childhood unintentional injuries surveillance done in five major cities of LMICs suggested that falls (50.4%) and road traffic injuries (16.4%) were the most common and affect boys more often than girls (64.7% vs. 35.3%) [ 13 , 14 ]. Studies on the pediatric ED disease spectrum in developing countries show that common presenting complaints tend to be fever, upper respiratory tract infection and diarrhea [ 9 - 12 ], and common final diagnoses are upper respiratory tract infection (26.7%), viral syndrome (13.1%) and gastroenteritis (10.7%) [ 9 - 12 ]. Therefore, the majority of chief complaints and final diagnoses are infection-related (up to 64%) [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the absence of allergen, even exposure to unrelated antigens may trigger shortness of breath and wheezing, again limiting lung function and thus, seriously affecting the patients’ quality of life. Pallor is an additional well known clinical sign of severe asthma and has recently been described to occur in 10% of emergency cases [5].…”
Section: Introductionmentioning
confidence: 99%